2018
DOI: 10.1111/jnc.14463
|View full text |Cite
|
Sign up to set email alerts
|

The orphan G‐protein‐coupled receptor 75 signaling is activated by the chemokine CCL5

Abstract: The chemokine CCL5 prevents neuronal cell death mediated both by amyloid β, as well as the human immunodeficiency virus viral proteins gp120 and Tat. Because CCL5 binds to CCR5, CCR3 and/or CCR1 receptors, it remains unclear which of these receptors plays a role in neuroprotection. Indeed, CCL5 also has neuroprotective activity in cells lacking these receptors. CCL5 may bind to a G-protein-coupled receptor 75 (GPR75), which encodes for a 540 amino-acid orphan receptor of the Gqα family. In this study, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
(47 reference statements)
1
38
0
Order By: Relevance
“…The GPR75 antibody (ab75581) we used has been previously validated by Dedoni et al using control and CRISPR-Cas9 GPR75 knockout (KO) human neuroblastoma cells. Dedoni and coworkers reported a single band in untreated cells and no band in KO neuroblastoma cells ( 50 ). In the present study, we performed Western blot experiments ( n = 5) using ab75581 and LS-A1589 on whole brain homogenates and demonstrated that both of these antibodies identified a single specific band at the expected molecular weight of 59 kDa for GPR75 ( Figure 1A ) and was absent in lysate from HEK293 cells ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPR75 antibody (ab75581) we used has been previously validated by Dedoni et al using control and CRISPR-Cas9 GPR75 knockout (KO) human neuroblastoma cells. Dedoni and coworkers reported a single band in untreated cells and no band in KO neuroblastoma cells ( 50 ). In the present study, we performed Western blot experiments ( n = 5) using ab75581 and LS-A1589 on whole brain homogenates and demonstrated that both of these antibodies identified a single specific band at the expected molecular weight of 59 kDa for GPR75 ( Figure 1A ) and was absent in lysate from HEK293 cells ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…CYP4A and GPR75 expression in the hippocampus, entorhinal cortex and corpus callosum may play a role in Alzheimer's disease and vascular dementia. Expression in these regions could have a functional significance that may help explain cognitive impairment and white matter changes observed in human studies examining CYP4A genetic variants (10) and studies in animals examining GPR75's role in neurodegeneration and amyloid-β accumulation (50).…”
Section: Discussionmentioning
confidence: 99%
“…After secretion of this chemokine outside the cell, two amino acids are truncated from the N-terminus by CD26/dipeptidyl peptidase IV (DPPIV), resulting in an increased affinity to CCR5 and reduced affinity to CCR1 and CCR3 [ 41 ]. CCL5 is also a ligand for G-protein-coupled receptor 75 (GPR75), whose expression occurs on brain nerve cells [ 42 , 43 ]. The effect of CCL5 is mitigated by the atypical chemokine receptor 2 (ACKR2)/D6, which reduces the level of this chemokine [ 44 , 45 , 46 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%
“…We reported that GPR75 is highly expressed in the brain and cerebral vasculature at protein levels in rats [40], and it is highly expressed at mRNA levels in the brain in humans (Human Protein Atlas: ); however, the exact cellular localization and roles of GPR75 in the brain are yet to be determined [41]. It is interesting that CCL5 is highly expressed in the cerebral vasculature in Alzheimer’s patients [42], which prevents amyloid β-induced neuronal cell death via activation of GPR75 [43]. High doses of 20-HETE also activate GPR40 in the pancreatic islet cells to regulate insulin secretion [44], but epoxyeicosatrienoic acids (EETs) activate GPR40 in endothelial, smooth muscle cells and arteries resulting in vasodilation [45].…”
Section: 20-hete In Hypertensionmentioning
confidence: 99%